1986
DOI: 10.1017/s0022172400062550
|View full text |Cite
|
Sign up to set email alerts
|

The seasonality of bacterial quality of water in a tropical developing country (Sierra Leone)

Abstract: SUMMARYNatural water sources used as drinking-water supplies by rural settlements in Sierra Leone were examined monthly over a one-year period to detect any seasonal variations in bacterial quality. The 37 'C colony count, levels of selected faecal indicator bacteria and the incidence of Salmonella spp. were monitored. A seasonality was demonstrated for all the variables, counts generally increasing with the progression of the dry season, culminating in peaks at the transition from dry to wet season. Some comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…These results confirm the findings of other studies which have found highest bacterial counts in the transition between the dry and wet seasons (Moore, de la Cruz & Vargas-Mendez, 1965;Feachem, 1974;Barrell & Rowland, 1979;Wright, 1986). In countries with pronounced dry and wet seasons, many of the sources available in the wet season dry up completely as the dry season progresses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm the findings of other studies which have found highest bacterial counts in the transition between the dry and wet seasons (Moore, de la Cruz & Vargas-Mendez, 1965;Feachem, 1974;Barrell & Rowland, 1979;Wright, 1986). In countries with pronounced dry and wet seasons, many of the sources available in the wet season dry up completely as the dry season progresses.…”
Section: Discussionsupporting
confidence: 91%
“…This seasonality varies by geographical area and the accompanying pattern of rainfall, temperature, type of water source and human behaviour. Generalizations about the peak pollution period cannot be made (Wright, 1986), as demonstrated by the contradictory findings of a number of studies from different countries (Feachem, 1974;Feachem et al 1978;Muhammed & Morrison, 1975;Barrell & Rowland, 1979;Bagde & Varma, 1982;Wright, 1986). Some studies have examined the transition periods between seasons and found a peak in the level of contamination at the start of the rains (Moore, de la Cruz & Vargas-Mendez, 1965;Feachem, 1974;Barrell & Rowland, 1979;Wright, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been recognized that total coliform proliferate in nature [6]. Data have also shown that fecal coliform, E. coli, and entorococci are found in the environment in the absence of a known sewage source of contamination [7][8][9] and have been shown to multiply within warm tropical environments [10][11][12][13][14]. Given the problems associated with microbial regrowth the State of Hawaii currently utilizes C. perfringens, a spore-forming obligate anaerobe, to supplement its beach water monitoring program.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial contamination of drinking water had been reported in various communities in the developing world [1][2][3][4][5][6][7][8]. Non-treatment or insufficient treatment of drinking water to acceptable international standards has been noted in such countries [6].…”
Section: Introductionmentioning
confidence: 99%